2002
DOI: 10.1182/blood-2002-01-0195
|View full text |Cite
|
Sign up to set email alerts
|

Internal tandem duplication of FLT3 in relapsed acute myeloid leukemia: a comparative analysis of bone marrow samples from 108 adult patients at diagnosis and relapse

Abstract: Analysis of internal tandem duplications of FLT3 (FLT3/ITD) was performed on bone marrow samples obtained at diagnosis and relapse from 108 adult patients with de novo acute myeloid leukemia (AML) to determine the role of this mutation in leukemic relapse. Eighty-three patients had wild-type FLT3 at both diagnosis and relapse, 16 had FLT3/ITD at both stages, whereas 8 had acquired the mutation and 1 had lost it at relapse. Using Genescan analysis, we found that FLT3/ ITD levels at first relapse were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
211
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(225 citation statements)
references
References 28 publications
8
211
2
4
Order By: Relevance
“…One possibility is that FLT3 mutations may emerge owing to the instability of the tumor genome. 24,25 The higher frequency of cytogenetic clonal evolution known to be associated with FLT3 mutations found in this study potentially supports this possibility. A second possibility is that, leukemia cells with FLT3 mutations may be present in bone marrow at time of initial diagnosis in a very small number that is below the level of detection of the assays to assess FLT3.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…One possibility is that FLT3 mutations may emerge owing to the instability of the tumor genome. 24,25 The higher frequency of cytogenetic clonal evolution known to be associated with FLT3 mutations found in this study potentially supports this possibility. A second possibility is that, leukemia cells with FLT3 mutations may be present in bone marrow at time of initial diagnosis in a very small number that is below the level of detection of the assays to assess FLT3.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have observed FLT3 mutation status changes in small subsets of acute myeloid leukemia patients and have implied the prognostic importance. 10,16,[21][22][23][24][25][26][27][28][29] In aggregate, these data suggest that gain of FLT3 mutations may be associated with worse prognosis. 24,27,29,33 These patients also seem not to benefit from intensifying chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, allele burden of FLT3-ITD is a key predictor of response to FLT3 inhibitor therapy. 79,80 In vitro studies of FLT3-ITDpositive cell lines demonstrated that relapsed samples and samples with a high mutant allele burden were more likely to be responsive to cytotoxicity from FLT3 inhibition compared with the samples obtained at diagnosis or those with a low mutant allele burden. 78 In these samples with lower FLT3-ITD allele burden, inhibition of FLT3 activity frequently did not result in cell death, suggesting that AML in patients with earlier stage disease and lower FLT3-ITD allele burden may not be addicted to FLT3 signaling for survival and proliferation.…”
Section: Quizartinib (Ac220)mentioning
confidence: 99%